Using the Box-Cox transformation to approximate the shape of the relationship between CO₂ emissions and GDP: A note - Mariana Conte Grand; Vanesa D'Elia (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2013)
With CAIT WRI data for those countries which submitted quantifiable CO2 emission caps under the Copenhagen Agreement, this note supports the existence of a long run relationship between CO2 emissions and GDP in 11 of the 26 countries in our sample over the period 1980-2008. However, the functional specification of that relationship is not homogenous among nations, being linear for 2 countries, log-log for 2 other cases, while the relationship follows a Box-Cox functional form for 7 nations. Elasticities of the emissions-income relationship also differ among counties. But in most cases (8 out of 11), the magnitude of the average elasticity is less than 1 (emissions increase less than GDP).
Keywords: Q01; Q54; O44; 330; CO2 emissions; sustainable development; Box-Cox